2006
DOI: 10.1021/bi060500q
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Analogues of Parathyroid Hormone:  Effect of C-Terminus Function on Helical Structure, Stability, and Bioactivity

Abstract: We have studied the effects of C-terminal group modifications (amide, methylamide, dimethylamide, aldehyde, and alcohol) on the conformation, adenylyl cyclase stimulation (AC), or binding of parathyroid hormone (hPTH) analogues, hPTH(1-28)NH(2) and hPTH(1-31)NH(2). hPTH(1-31)NH(2) has a C-terminal alpha-helix bounded by residues 17-29 [Chen, Z., et al. (2000) Biochemistry 39, 12766]. In both cases, relative to the natural analogue with a carboxyl C-terminus, the amide and methylamide had increased helix conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The modular behavior of the CRF receptors with the ECD1 as the major peptide binding domain is also reported for other members of the peptide hormone GPCR family such as parathyroid hormone (12,40,41,43,44) and the SCR motif of the ECD1 is predicted to be conserved in all of the ECD1s of the B1 family of GPCRs (18). The modular property is also present for various peptide hormones such as parathyroid hormone (45). Typically the N-terminal segment of the ligand is responsible for receptor signaling, whereas the C-terminal segment is an important determinant for the receptor binding (45,46) and may interact with the ECD1 of the receptor as evidenced by cross-linking (47).…”
Section: Crf Ligand-receptor Interactions Have a Common Binding Modementioning
confidence: 65%
See 1 more Smart Citation
“…The modular behavior of the CRF receptors with the ECD1 as the major peptide binding domain is also reported for other members of the peptide hormone GPCR family such as parathyroid hormone (12,40,41,43,44) and the SCR motif of the ECD1 is predicted to be conserved in all of the ECD1s of the B1 family of GPCRs (18). The modular property is also present for various peptide hormones such as parathyroid hormone (45). Typically the N-terminal segment of the ligand is responsible for receptor signaling, whereas the C-terminal segment is an important determinant for the receptor binding (45,46) and may interact with the ECD1 of the receptor as evidenced by cross-linking (47).…”
Section: Crf Ligand-receptor Interactions Have a Common Binding Modementioning
confidence: 65%
“…The modular property is also present for various peptide hormones such as parathyroid hormone (45). Typically the N-terminal segment of the ligand is responsible for receptor signaling, whereas the C-terminal segment is an important determinant for the receptor binding (45,46) and may interact with the ECD1 of the receptor as evidenced by cross-linking (47). Furthermore, the bioactive conformations of various peptide hormones are proposed to be of amphipathic helical nature (48), similar to the conformation observed for astressin.…”
Section: Crf Ligand-receptor Interactions Have a Common Binding Modementioning
confidence: 99%
“…Crystals of the purified MBP-PTH1R-ECD bound to a synthetic PTH fragment (residues [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] were grown in hanging drops containing a reservoir solution of 100 mM sodium cacodylate (pH 6.5) and 30% (vol/vol) polypropylene glycol P400 (PPG P400). Diffraction data were collected at 21-ID-D (LS-CAT) of the Advanced Photon Source at Argonne National Laboratory (Argonne, IL).…”
Section: Methodsmentioning
confidence: 99%
“…Studies with ligand variants and receptor/ligand photo cross-linking indicate that the Nterminal fragment of PTH (residues 1-14) binds to the transmembrane domain, albeit with low affinity, and that it is able of activating the receptor (26,27). The C-terminal fragment of PTH (residues 15-34) binds to the N-terminal ECD of the receptor to confer high affinity and specificity to the receptor (28,29). This ''two-domain'' model of PTH binding and activation is further supported by studies with chimeric ligands and receptors (30)(31)(32) and has since been demonstrated for other class B GPCR molecules (33)(34)(35).…”
mentioning
confidence: 99%
“…The hPTH (1-34) is defined as a 'two-domain model', in which the N-terminal region (residues 1-14, hPTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)) recognizes and activates the PTH1R by attaching to the extracellular loops and the juxtamembrane regions of its transmembrane domain [10]. The C-terminal region (residues 15-34, hPTH (15-34)) comprises a high-affinity binding domain that binds to the PTH1R N-terminal ECD, resulting in high receptor affinity and specificity [11].…”
Section: Introductionmentioning
confidence: 99%